Gut Microbiota and Clinical Features Distinguish Colonization With Klebsiella pneumoniae Carbapenemase-Producing Klebsiella pneumoniae at the Time of Admission to a Long-term Acute Care Hospital. (31st July 2018) - Seekatz, Anna M; Bassis, Christine M; Fogg, Louis; Moore, Nicholas M; Rhee, Yoona; Lolans, Karen; Weinstein, Robert A; Lin, Michael Y; Young, Vincent B; Hayden, Mary K; ,
Abstract: Background: Identification of gut microbiota features associated with antibiotic-resistant bacterial colonization may reveal new infection prevention targets. Methods: We conducted a matched, case–control study of long-term acute care hospital (LTACH) patients to identify gut microbiota and clinical features associated with colonization by Klebsiella pneumoniae carbapenemase-producing Klebsiella pneumoniae (KPC-Kp), an urgent antibiotic resistance threat. Fecal or rectal swab specimens were collected and tested for KPC-Kp; 16S rRNA gene-based sequencing was performed. Comparisons were made between cases and controls in calibration and validation subsamples using microbiota similarity indices, logistic regression, and unit-weighted predictive models. Results: Case (n = 32) and control (n = 99) patients had distinct fecal microbiota communities, but neither microbiota diversity nor inherent clustering into community types distinguished case and control specimens. Comparison of differentially abundant operational taxonomic units (OTUs) revealed 1 OTU associated with case status in both calibration (n = 51) and validation (n = 80) subsamples that matched the canonical KPC-Kp strain ST258. Permutation analysis using the presence or absence of OTUs and hierarchical logistic regression identified 2 OTUs (belonging to genus Desulfovibrio and family Ruminococcaceae ) associated with KPC-Kp colonization. Among clinical variables, the presence of a decubitus ulcer alone was independently and consistently associated with case status. Combining the presence of the OTUs Desulfovibrio and Ruminococcaceae with decubitus ulcer increased the likelihood of KPC-Kp colonization to >38% in a unit-weighted predictive model. Conclusions: We identified microbiota and clinical features that distinguished KPC-Kp gut colonization in LTACH patients, a population particularly susceptible to KPC-Kp infection. These features may warrant further investigation as markers of risk for KPC-Kp colonization.